The impact of cost changes on industry dynamics - James E. Prieger (University of California, Department of Economics, 2005)
This paper inquires into the response of industry dynamics to increases in costs. We show that increases in marginal and fixed costs may have interesting, non-obvious effects on entry and exit. Before costs change, the model exhibits behavior that matches many industries such as manufacturing and retail: fewer but larger firms over time, and significant amounts of entry and exit. When costs rise, price rises and the market quantity supplied falls, but the amount of entry and exit may rise or fall. The most intuitive outcome from a cost increase is the competitor neutral case, in which entry decreases and exit increases. Two other possible cases are the entrant favoring case, in which entry and exit both increase, and the incumbent favoring case, in which entry and exit both decrease. The model places restrictions on which outcomes are possible given which costs rise (marginal or fixed). The entrant favoring case can arise only from an increase in marginal cost, which favors small entering firms relative to larger incumbents. The incumbent favoring case can come about only from an increase in fixed cost, which favors incumbents with their larger market share relative to small entrants. These restrictions allow one to infer the nature of the cost increases even when costs are not directly observed. The model can be used to examine the impacts of cost-increasing regulation or exogenous process innovation on industry dynamics.
Keywords: D43; L11; 330